(untitled) (Global Journal of Computer Science and Technology, 2013)
In mobile ad hoc networks nodes can move freely and link node failures occur frequently This leads to frequent network partitions which may significantly degrade the performance of data access in ad hoc networks When the network partition occurs mobile nodes in one network are not able to access data hosted by nodes in other networks In mobile ad hoc network some nodes may selfishly decide only to cooperate partially or not at all with other nodes These selfish nodes could then reduce the overall data accessibility in the network In this work the impact of selfish nodes in a mobile ad hoc network from the perspective of replica allocation is examined We term this selfish replica allocation A combined credit risk method collaborative watchdog is proposed to detect the selfish node and also apply the SCF tree based replica allocation method to handle the selfish replica allocation appropriately The proposed method improves the data accessibility reduces communication cost and average query delay and also to reduce the detection time and to improve the accuracy of watchdogs in the collaborative method